Analisis Indikasi Manipulasi Laporan Keuangan dengan Metode Cash Flow Shenanigans pada PT FKS Food Sejahtera periode 2019-2024 - Carissa Laura Eka Putri; Esty Apridasari; Thoyibatun Nisa; Northa Idaman (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to analyze indications of financial statement manipulation using the Cash Flow Shenanigans method at PT FKS Food Sejahtera Tbk (AISA) for the 2019–2024 period. The research employs a quantitative method using secondary data derived from the company’s annual financial statements. The results indicate signs of manipulation across all three categories of Cash Flow Shenanigans. In Shenanigans No. 1, the ratios of operating cash flow to current liabilities and accounts receivable to operating cash flow show extreme fluctuations and inconsistencies between net income and operating cash flow, suggesting potential accrual manipulation. In Shenanigans No. 2, the Free Cash Flow (FCF) ratio exhibits a significantly negative pattern during 2020–2022, indicating the possible reclassification of operating expenses as investment activities. Meanwhile, in Shenanigans No. 3, the Days Payable Outstanding and inventory-to-operating cash flow ratios reveal efforts to manage payment timing and control inventory levels to enhance the appearance of operating cash flow performance. Overall, the findings reveal strong indications of cash flow shenanigans during 2020–2022, possibly triggered by the impact of the COVID-19 pandemic. Although the company’s cash flow condition improved in 2023–2024, there remain signs of manipulative window dressing practices aimed at portraying a healthier performance, which should be carefully monitored by auditors, investors, and capital market regulators.